2018 Fourth International Conference on Information Retrieval and Knowledge Management (CAMP) 2018
DOI: 10.1109/infrkm.2018.8464819
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using the Position as Feature for Idea Identification from Text

Abstract: Abstracts of research papers are meant to provide a brief condensed overview of respective research topics. This includes a glimpse of the new idea that the paper proposes. The aim of the research presented here is to investigate the feasibility of the effect of text position in the idea identification. The abstracts are structured in the form of introduction, body, and conclusion. It is hypothesized that research ideas tend to be phrased in conclusion section of paper abstracts. 25 abstracts of the scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A modified idea mining model to capture the term position within text phrases is utilized [3], in which a term position measure is incorporated into the idea mining model, proposed in [29], to enhance the performance. This modified model assigned as a probability weight to be incorporated into the less considered sub-measure which enables calculating the importance of the position for the candidate ideas.…”
Section: Idea Mining Model Based On Text Positionmentioning
confidence: 99%
See 2 more Smart Citations
“…A modified idea mining model to capture the term position within text phrases is utilized [3], in which a term position measure is incorporated into the idea mining model, proposed in [29], to enhance the performance. This modified model assigned as a probability weight to be incorporated into the less considered sub-measure which enables calculating the importance of the position for the candidate ideas.…”
Section: Idea Mining Model Based On Text Positionmentioning
confidence: 99%
“…Authors in [3] performed an experimental investigation by implementing 10000 combinations and produce a new set of random weights based on rules assigned for discovering the best ranking. The findings of these experiments have shown that the highest MAP obtained when integrating position measure highly indicated ideas in conclusion sections more than other sections.…”
Section: Idea Mining Model Based On Text Positionmentioning
confidence: 99%
See 1 more Smart Citation